Follow-up of Differentiated Thyroid Cancer: What is the Value of FDG and Sestamibi in the Diagnostic Algorithm? - Dietlein, M.; Scheidhauer, K.; Voth, E.; Theissen, P.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 1998)
Aim: FDG-PET and MIBI-scintigraphy with SPECT were compared to [131I]-whole-body scintigraphy (WBS) and morphologic imaging in the follow-up of differentiated thyroid cancer. Their influence on therapy-planning was analysed. Methods: In 50 consecutive patients (papillary/ follicular/variants of a follicular carcinoma: 33/13/4; primary status: pTI/2/3/4: 3/16/9/22) FDG-PET of neck/chest and MIBI-whole-body scan including SPECT were performed during hypothyreosis and before WBS. Morphologic imaging was done by MRI in all and by CT of the lung without contrast media in 21 patients. Results: The complete extent of metastases was detected by FDG-PET in 11 and by MIBI-scintigraphy also in 11 of 22 patients with evidence of disease. The combined evaluation of WBS and FDG-PET as well as of WBS and MIBI-scintigraphy held true in 18 of 22 patients. Limiting FDG-PET or MIBI-scintigraphy to patients with elevated thyroglobulin (Tg)-levels and negative WBS only, would not, therefore, alter the sensitivity of this algorithm. The diagnostic benefit of FDG-PET and MIBI-scintigraphy was confined to lymph node metastases. The 1 cm limit for lymph node size in morphologically based imaging did not apply to FDG-PET and MIBI-scintigraphy. None of the 6 patients with small (<1 cm) pulmonary metastases showed either FDG- or MIBI-uptake, but could be diagnosed by spiral-CT. Conclusion: WBS cannot be replaced by FDG-PET or MIBI-scintigraphy; neither of the latter was better than the other. Rising Tg-levels, negative WBS and the exclusion of pulmonary metastases by spiral-CT define the constellation in which FDG-PET and MIBI-scintigraphy can provide data of therapeutic relevance.
Keywords: Thyroid cancer; FDG-PET; Sestamibi; Radioiodine; Scintigraphy